In vivo Study of the Histone Chaperone Activity of Nucleolin by FRAP - Xavier Gaume; Karine Monier; Françoise Argoul; Fabien Mongelard; Philippe Bouvet (Biochemistry Research International)
Nucleolin is a major nucleolar protein involved in various aspects of ribosome biogenesis such as regulation of polymerase I transcription, pre-RNA maturation, and ribosome assembly. Nucleolin is also present in the nucleoplasm suggesting that its functions are not restricted to nucleoli. Nucleolin possesses, in vitro, chromatin co-remodeler and histone chaperone activities which could explain numerous functions of nucleolin related to the regulation of gene expression. The goal of this report was to investigate the consequences of nucleolin depletion on the dynamics of histones in live cells. Changes in histone dynamics occurring in nucleolin silenced cells were measured by FRAP experiments on eGFP-tagged histones (H2B, H4, and macroH2A). We found that nuclear histone dynamics was impacted in nucleolin silenced cells; in particular we measured higher fluorescence recovery kinetics for macroH2A and H2B but not for H4. Interestingly, we showed that nucleolin depletion also impacted the dissociation constant rate of H2B and H4. Thus, in live cells, nucleolin could play a role in chromatin accessibility by its histone chaperone and co-remodeling activities.